High flux femtosecond x-ray emission from the electron-hose instability in laser wakefield accelerators - C. F. Dong (Physical Review Accelerators and Beams, 2018)
Bright and ultrashort duration x-ray pulses can be produced by through betatron oscillations of electrons during laser wakefield acceleration (LWFA). Our experimental measurements using the Hercules laser system demonstrate a dramatic increase in x-ray flux for interaction distances beyond the depletion/dephasing lengths, where the initial electron bunch injected into the first wake bucket catches up with the laser pulse front and the laser pulse depletes. A transition from an LWFA regime to a beam-driven plasma wakefield acceleration regime consequently occurs. The drive electron bunch is susceptible to the electron-hose instability and rapidly develops large amplitude oscillations in its tail, which leads to greatly enhanced x-ray radiation emission. We measure the x-ray flux as a function of acceleration length using a variable length gas cell. 3D particle-in-cell simulations using a Monte Carlo synchrotron x-ray emission algorithm elucidate the time-dependent variations in the radiation emission processes.